Realities and Realizations: Reflections on a Social Work Exchange Program between the United States and China - Cullen, Jennifer; Haney, Jolynn L.; Houser, Linda; Cao, Jun; Mi, Xi (Journal of International Students, 2016)
China has a long and complex history of political, economic, and educational shifts that have resulted in and from changing cultural values. Over time, the significance and format of social work education in China has changed, as has the need for professionally educated social workers that can support the ever-evolving social needs of China. To this end, some Chinese schools have begun to partner with schools in the U.S. to support the professionalizing of social work in China. This article presents the reflections of faculty and students involved in an exchange program for Chinese students to study in a U.S.-based master of social work program. Expectations, realities, needs, and recommendations of both faculty and students are discussed.